THE CLINICAL MANIFESTATIONS OF SCABIES IN PATIENTS PRESENTING TO DERMATOLOGY OUTPATIENTS DEPARTMENT AT AYUB TEACHING HOSPITAL, ABBOTTABAD - Arshad Pirzada, Durreshaehwar; Abdullah, Sumaira; Maria Syed; Zarar Bin Jamil; Muhammad Khubaib Ullah (Journal of Ayub Medical College Abbottabad, 2024)
Background: Scabies is a significant skin problem in the developing countries due to its increased incidence, complications and financial implications. The aim of this study is to highlight the endemicity of scabies in our population and its clinical manifestations including various complications. The study was conducted to determine the frequency and clinical manifestations of scabies in patients presented to dermatology outpatient department (opd), Ayub teaching hospital, Abbottabad. Methods: This cross-sectional study was conducted on 1404 patients suspected to have scabies. The demographic and clinical features of scabies presentation was recorded on a questionnaire by interview. The skin scrapings were observed under microscope after preparing 10% KOH mount. Results: During the study period, out of 1404 patients, 339 patients with scabies were identified, with frequency 24.14%. The mean age calculated was 21.18 years. The frequency of scabies was 56% (190) in males while 44% (149) in females. All studied patients had pruritis (male =190. female =149). 89.1% had papules, 39.8% had excoriations on their bodies, 15.6% had impetiginization, 12.7% had eczema and only 3.2% of total had blisters. It was observed that complications like impetigo, eczema, blisters were more in patients living in unfavorable conditions. Conclusion: The results of the study showed that scabies is a common skin infestation in our population. It is recommended that awareness programs be implemented at primary healthcare level so that necessary measures can be taken to control this preventable and communicable disease.